2014
DOI: 10.1242/dev.109041
|View full text |Cite
|
Sign up to set email alerts
|

The origin and loss of periodic patterning in the turtle shell

Abstract: The origin of the turtle shell over 200 million years ago greatly modified the amniote body plan, and the morphological plasticity of the shell has promoted the adaptive radiation of turtles. The shell, comprising a dorsal carapace and a ventral plastron, is a layered structure formed by basal endochondral axial skeletal elements (ribs, vertebrae) and plates of bone, which are overlain by keratinous ectodermal scutes. Studies of turtle development have mostly focused on the bones of the shell; however, the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
140
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(150 citation statements)
references
References 44 publications
(55 reference statements)
9
140
0
1
Order By: Relevance
“…In addition, loss-of-function mutations in Fgf receptors were found to be associated with independent scale loss in two cyprinid lineages (domesticated carp 15 ; Phoxinellus 16 ). These insights are consistent with roles for Fgf signaling in the development of other epithelial appendages, including feathers 17 and turtle shell scutes 18 . In instances of scale loss, the causative mutation likely disrupts placode formation, leading to loss of the organ.…”
Section: Introductionsupporting
confidence: 75%
“…In addition, loss-of-function mutations in Fgf receptors were found to be associated with independent scale loss in two cyprinid lineages (domesticated carp 15 ; Phoxinellus 16 ). These insights are consistent with roles for Fgf signaling in the development of other epithelial appendages, including feathers 17 and turtle shell scutes 18 . In instances of scale loss, the causative mutation likely disrupts placode formation, leading to loss of the organ.…”
Section: Introductionsupporting
confidence: 75%
“…Instead, its differentiation is probably a plastic side-effect of constrained scapula growth within an exceptionally flattened shell, as suggested by the positive correlation of scapula mass and shell height. These observations contribute to a growing consensus on fundamental developmental differences between hard-and soft-shelled turtles [3,[8][9][10]17]. Skeletal morphology may vary due to epigenetic tissue remodelling induced by novel mechanical stimuli experienced in development [2,23].…”
Section: Discussionmentioning
confidence: 88%
“…Exploring this ecological diversity may demonstrate how developmental change has contributed to subsequent evolution of the basic turtle body plan [4]. Recent studies focusing on two distantly related species revealed surprising variation in how the shell forms [8][9][10]. Still, as an outcome of shell development, all extant species share a similar anatomical configuration: the shoulder girdle is situated anteriorly to the rib cage and is encapsulated within the shell [11].…”
Section: Introductionmentioning
confidence: 99%
“…Care should be taken in the future as to the expression patterns found and the conclusions to be drawn from them. We propose that future research must be very specific in (i) the stage of embryos assayed, always according to stan- (ii) utilization of unequivocal probes, with special care in the case of close paralogues (for instance, by avoiding probes based in conserved domains); and (iii), when possible, use embryos from different turtle clades, in order to be able to, on the one hand, infer common patterns, and on the other to distinguish between different developmental modules, as soft-shelled turtles are expected to have lost patterns seen related with scutes development (see Moustakas-Verho et al, 2014).…”
Section: B Amentioning
confidence: 99%